(3eLehYI aj GdcjejGAs
(3ChdgG (B:s
(3UaI JOHjQ GdUfYI Ydi QCi HYV GdadGSaI JCNP Ydi HQcI Gddg hYhfg ef GdMLQ GdcQje GdcQi GdTcd s
(3BNQgG (B:s
(3hjchf GNQGL GdUHZ ef GdejGg GdKdGKI GdCTjGA GdNGQLI fe GdeZfSjG jchf ef GdejGg GdKdGKI HhRf YOd Ef TGA Gddg JYGdi JUd Hefg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs